Synthesis and Characterization of Palladium (II) Complexes Containing Mixed Ligands with Pyrrolidine Dithiocarbamate and Phosphines - Hussein, Mousa S (Al-Nahrain Journal of Science, 2018)
This work includes preparation and characterization of new four mono nuclear complexes of palladium metal ion result from treating palladium chloride with ammonium pyrrolidine dithiocarbamate (PDTC), tertiary phosphines(dppe, dppp) and 2-phenyl pyridine (Hppy) in different molar ratios. All complexes have been characterized by spectroscopic methods{IR, UV-Vis, 1HNMR} spectroscopy, in addition to elemental analysis (C.H.N) and conductivity measurement. pyrrolidine dithiocarbamate‎ ligand behaves like bidentate in the complexes [Pd(PDTC)(dppe)]Cl and [Pd(PDTC)(ppy)] but it behaves as mono dentate in the complexes [Pd(PDTC)2(dppp)] and [Pd(PDTC)2(dppe)], while tertiary phosphines and 2-phenyl pyridine behave like bidentate ligand.